1998
DOI: 10.23986/afsci.5611
|View full text |Cite
|
Sign up to set email alerts
|

Salt content labelling of foods in supermarkets in Finland

Abstract: The aim of the study was to assess the extent to which lightly salted food products are included in the assortments of Finnish supermarkets and prominently placed on shelves. The study was carried out in eastern Finland in four supermarkets of different food chains. Six food groups of importance for people's salt intake were considered. The food labels of 689 packaged food products were checked for salt and sodium information on the basis of Finnish regulations on salt. Products with reduced salt contents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…One way in which this can be achieved is by clearer salt/sodium labelling. There has been some ambiguity surrounding the labelling of salt/sodium; however, there is evidence to suggest that retailers across Europe are increasingly aware of the need for clearer labelling and have been pro‐active in addressing this issue 37 . With combined efforts from retailers in respect of salt/sodium labelling and the development of reduced salt foods, consumers can then make informed purchasing decisions, which will help towards an improved diet.…”
Section: Discussionmentioning
confidence: 99%
“…One way in which this can be achieved is by clearer salt/sodium labelling. There has been some ambiguity surrounding the labelling of salt/sodium; however, there is evidence to suggest that retailers across Europe are increasingly aware of the need for clearer labelling and have been pro‐active in addressing this issue 37 . With combined efforts from retailers in respect of salt/sodium labelling and the development of reduced salt foods, consumers can then make informed purchasing decisions, which will help towards an improved diet.…”
Section: Discussionmentioning
confidence: 99%
“…In 1992, Finland legally established salt content‐based food categories. Thus, in the case of bread, those products with a salt content of more than 1.3% must be labeled as “heavily salted,” whereas those with a salt content of less than 0.7% can be labeled as “lightly salted.” By 1998, a survey of Finnish supermarkets found that only 0.9% of bread was heavily salted, whereas 92.5% was normally salted (salt content of between 0.7% and 1.3%), and 6.6% was lightly salted 136 . Apart from the above‐mentioned salt‐reduction strategies in Finland, this labeling information is considered to have had a marked impact on consumer choice 137 .…”
Section: The Commercial Viewpointmentioning
confidence: 99%
“…By 1998, a survey of Finnish supermarkets found that only 0.9% of bread was heavily salted, whereas 92.5% was normally salted (salt content of between 0.7% and 1.3%), and 6.6% was lightly salted. 136 Apart from the abovementioned salt-reduction strategies in Finland, this labeling information is considered to have had a marked impact on consumer choice. 137 In light of the importance of labeling, it would be important to establish a Europewide symbol to identify those products with a reduced salt content, as based on pre-established limits, which, in the case of bread, could be set to 1%.…”
Section: Product Communication and Informationmentioning
confidence: 99%
“…The high salt levels are unattractive to consumers who are demanding healthier foods. It is well known that a lower salt intake enables healthy blood pressure levels to be maintained (Narhinen et al, 1998). However, lower salt levels in these products reduce the amount of exuded protein, which acts as a binding agent and affects the protein aggregation mechanism and the overall quality of the final product (Uresti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%